A history of the Jewish War: A.D. 66-74 - Mason, Steve (Cambridge University Press, 2016)
"A conflict that erupted between Roman legions and some Judaeans in late AD 66 had an incalculable impact on Rome's physical appearance and imperial governance; on ancient Jews bereft of their mother-city and temple; and on early Christian fortunes. Historical scholarship and cinema alike tend to see the conflict as the culmination of long Jewish resistance to Roman oppression. In this volume, Steven Mason re-examines the war in all relevant contexts (such as the Parthian dimension, and Judaea's place in Roman Syria) and phases, from the Hasmoneans to the fall of Masada. Mason approaches each topic as a historical investigation, clarifying problems that need to be solved, understanding the available evidence, and considering scenarios that might explain the evidence. The simplest reconstructions make the conflict more humanly intelligible while casting doubt on received knowledge"--